RURAL INDIAN HEALTH-CARE: ASSESSING PATIENT SATISFACTION USING THE SERVPERF MODEL - Chawngzikpuii, Ishanika; Lalromawia, K (Bangladesh Journal of Multidisciplinary Scientific Research, 2024)
The assessment of health-care service quality has evolved significantly, shifting from purely clinical metrics to encompass patient experiences and perceptions. This paradigm shift recognizes that patient viewpoints are crucial in evaluating and improving health-care services. However, there is a significant gap in understanding these perceptions in rural health-care settings, particularly in developing countries. This study addresses this gap by examining patient-perceived service quality in rural Mizoram, India, employing the SERVPERF model to assess Primary Health Centers (PHCs). The study examines patient satisfaction, and a survey of 200 patients from 7 primary health centers was conducted to assess perceptions of service quality across five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Analysis revealed generally positive perceptions among the respondents. The Assurance dimension scored highest (M = 3.958), emphasizing the importance of staff knowledge and trustworthiness. Strong positive correlations were found between all dimensions (r > 0.3, p < 0.01). Binary logistic regression indicated all dimensions significantly predicted overall service quality (p < 0.001), with Tangibles showing the most substantial effect (Exp(β) = 3.501). These findings highlight the multifaceted nature of health-care service quality and suggest that while patients value competent and empathetic care, the physical environment significantly influences overall quality perceptions. The study provides insights for health-care managers in rural settings to enhance service quality through a holistic approach addressing clinical and non-clinical patient care aspects. JEL Classification Codes: I11, I18, M31, O15.